111 Comparison of Hounsfield Units Versus T-Score in Predicting Postoperative Proximal Junctional Kyphosis. (1st April 2022) - Mallory, Noah; Moranville, Robert; Gibbs, David C.; Keister, Alex; Munjal, Vikas; Maggio, Dominic; Grossbach, Andrew J.; Viljoen, Stephanus; Farhadi, Francis
Abstract : INTRODUCTION: Vertebral body (VB) bone quality is generally estimated indirectly via femoral neck dual-energy x-ray absorptiometry (DEXA) to counsel patients on their risk for development of proximal junctional kyphosis (PJK) after thoraco-lumbar fusion for adult spinal deformity. It is currently unknown whether direct measurement of VB bone quality through Hounsfield unit analysis (HUs) can successfully stratify patients on their risk of delayed complications. METHODS: 108 patients who underwent surgery for ASD were enrolled. Demographic characteristics, radiologic measurements, complication profile, and clinical outcomes were recorded both pre- and post-operatively. A Youden J-statistic was calculated based on an ROC analysis of the UIV Hounsfield unit data to give a single HU threshold to segregate patients into either a high or low HU group. Patient groups were then compared with respect to the mentioned clinical and radiographic outcome measures. RESULTS: Youden statistic revealed a HU threshold value of 126.8 for maximal group stratification. Significant change in proximal junctional cobb angle (PJCA) was observed between the low and high HU groups at one and two years (p < 0.0001 and p = 0.0001 respectively). This was not similarly seen in hip or spine DEXA analysis (p > 0.05). CONCLUSION: Assessment of bone quality via pre-operative measurement of the UIV VB HU can predict post-operative changes in PJCA. UIV HUs < 126.8 are associated with 2.8x elevated risk of developing post-operative PJK. Current standard of care measurement of bone quality via femoral neck DEXA is of more limited utility compared to HU analysis.